2017
DOI: 10.1017/s1742758417000200
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal incidence of insect pests in farmers’ cabbage fields in Senegal

Abstract: In Senegal, damage caused by insect pests is a major obstacle to seasonal stability and an increase in cabbage production. Little is known about the spatial and temporal distribution of cabbage pests, which makes the design of management recommendations to small-scale farmers challenging. The objectives of this study were to: (i) evaluate the status of insect pests observed in cabbage farmers’ fields; (ii) give information on the spatial and temporal distribution of key pests and (iii) assess the effect of tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…The highest thrips densities were found in the middle of tunnels. Similar observations have been made of the diamondback moth and the cabbage webworm in different crops [ 73 , 74 ]. The slope at the study site may have caused the middle of the tunnels to be warmer than the area by the tunnel openings due to the upwards wind, a factor which possibly also contributed to a higher number of thrips in the centre of the tunnels.…”
Section: Discussionsupporting
confidence: 83%
“…The highest thrips densities were found in the middle of tunnels. Similar observations have been made of the diamondback moth and the cabbage webworm in different crops [ 73 , 74 ]. The slope at the study site may have caused the middle of the tunnels to be warmer than the area by the tunnel openings due to the upwards wind, a factor which possibly also contributed to a higher number of thrips in the centre of the tunnels.…”
Section: Discussionsupporting
confidence: 83%
“…Cabbage ( B. oleracea var. capitata ) is a widely recorded host [ 15 ], and larvae of this insect are considered a pest on these crops, particularly in the subcontinent [ 17 , 18 , 19 , 20 , 21 ] and elsewhere [ 22 ]. Thakor and Patel [ 23 ] readily reared H. armigera on cabbage in the laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…The major pests in the current study have been identified as a significant threat to cruciferous crops in many countries (Yankanchi & Patil 2009;Reddy 2011;Labou et al 2017;Shah et al 2019) and insecticides, due to their rapid action, have been the most adopted control measure among growers, despite increasing realization of their undesired effects. IPM considers strategies that can limit or replace excessive reliance on pesticides in order to diminish negative effects while maintaining or improving pest control.…”
Section: Discussionmentioning
confidence: 92%